Kajian Teknis Penimbunan Batubara pada ROM Stockpile Untuk Mencegah Terjadinya Swabakar Di PT. Prima Dito Nusantara, Job Site KBB, Kabupaten Sarolangun, Provinsi Jambi - Alif Vito Palox; Rijal Abdullah; Yoszi Mingsi Anaperta (Departemen Teknik Pertambangan FT UNP, 2018)
Spontaneous combustion problems are often almost ignored, one of which occurred in ROM stockpile at PT. Prima Dito Nusantara (PDN) which is an important issue in the coal mine. Some of the factors that cause the occurrence of spontaneous combustion at the company was the lack of stockpile management such as the length of the stockpiling of coal, compaction method of the coal piles on a less good, there has been no temperature measurement of the coal piles, and a lack of prevention efforts as well as handling against spontaneous combustion. To find out when the estimated occurrence of spontaneous combustion then do the measurement temperature of the coal pile periodically by measurement point temperature on compaction with Excavator and compaction with Bulldozer. Measurement results showed on compaction with Excavator faster occurs spontaneous combustion symptoms when compared with compaction with Bulldozer. Where in compacting with the Excavator can be estimated to occur in week-9 with highest median temperature 42,22°C, compacting with Bulldozer can be estimated in week-15 with highest median temperature 39,10°C. Therefore, compaction with Bulldozer better applied than compacting with Excavator to reduce the occurrence of symptoms of spontaneous combustion of the coal piles at ROM stockpile. Keywords: Spontaneous Combustion, Stockpile Management, Excavator, Bulldozer, Temperature.